Interventions and Strategies to Improve Sexual and Reproductive Health Outcomes among Adolescents Living in Low- and Middle-Income Countries: A Systematic Review and Meta-Analysis - Salima Meherali; Mehnaz Rehmani; Sonam Ali; Zohra S. Lassi (MDPI AG, 2021)
Adolescent access to quality sexual and reproductive health and rights has been a major issue in most low- to middle-income countries (LMICs). This systematic review aims to identify the relevant community and school-based interventions that can be implemented in LMICs to promote adolescents' sexual and reproductive health and rights. We identified 54 studies, and our review findings suggested that educational interventions, financial incentives, and comprehensive post-abortion family planning services were effective in increasing their knowledge and use of Adolescent Sexual and Reproductive Health and Rights (ASRHR) services, such as contraception, which led to a decrease in unwanted pregnancies. However, we found inconclusive and limited evidence on the effectiveness of interventions for improved violence prevention and adolescent behavior towards safe sexual practices. More rigorous studies with long-term follow-ups are needed to assess the effectiveness of such interventions.